Metal-Based Drugs: Past, Present and Future (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The reprint entitled “Metal-Based Drugs: Past, Present, and Future” covers some recent research and review articles in the field of metal-based drugs used in medicine. By purpose and content, this Book is addressed to the vast number of life science researchers and health care workers (chemists, pharmacists, biochemists, physicists, and doctors). Our initiative to publish in Molecules Journal the Special Issue entitled “Metal-Based Drugs: Past, Present, and Future” was honored by 13 groups totaling 74 scientists from Asia (India, Saudi Arabia, and Taiwan), Europe (Bulgaria, France, Ireland, Italy, Romania, Spain, Switzerland, and the U.K.), North America (Canada), and Africa (Egypt and South Africa). The number of involved researchers and the geographic distribution of their academic institutions indicate the great interest of the worldwide scientific community in discovering new metal-based drugs that can treat different diseases.